Analysis of clinical characteristics and prognosis of patients with peripheral T-cell lymphoma. Issue 13 (2nd April 2021) - Liang, Xiao; Guo, Li; Hu, Xin; Li, Shan; Wen, Shujuan
Abstract: Background: This study aimed to explore the clinical characteristics, therapeutic efficacy and prognostic factors of peripheral T-cell lymphoma (PTCL). Methods: The clinical data of 119 PTCL patients who were admitted to the Xinjiang Medical University Affiliated Tumor Hospital from January 2010 to December 2017 were retrospectively analyzed, including the clinical characteristics, therapeutic efficacy, prognosis-related factors and treatments. Among the patients, 98 patients received antharcyclines-based therapeutic protocols, including Cyclophosphamide, Pirarubicin, Vincristine, Prednisone (CHOP) protocol and Cyclophosphamide, Pirarubicin, Vincristine, Prednisone, Etoposide (CHOPE) protocol, with median follow-up time of 32.5 months (2–166 months). The patients' clinical characteristics were analyzed, and COX ratio risk regression model was adopted to analyze the prognostic factors related with the survival rate of PTCL patients. Results: The 5-year overall survival (OS) rate was 46.4% and progression-free survival (PFS) rate was 42.7% in the 98 patients, and there were insignificant differences between patients with CHOP protocol and those with CHOPE protocol in the 5-year OS and PFS rates (OS: P  = 0.197, PFS: P  = 0.663). The univariate analysis results showed that different pathological types, Ann Arbor stage, Eastern Cooperative Oncology Group (ECOG) score ≥ 2, the number of extranodal lymphomas involved, Lactic dehydrogenase (LDH) level, presence/absence of bone marrow involved, international prognostic index (IPI) score, β2 microglobulin (β2 -MG) level and hemoglobin (Hb) level were poor prognosis factors influencing patients' OS and PFS rates ( P all < .05). Multivariate analysis demonstrated that different pathological types, Ann Arbor stage, presence/absence of bone marrow involved and Hb level were independent prognostic indicators influencing patients' OS and PFS rates ( P all < .05). Conclusion: PTCL is poor in therapeutic efficacy and prognosis, and different pathological types, Ann Arbor stage, presence/absence of bone marrow involved and Hb level are related with the prognosis of PTCL patients. Anemia occurring before the treatment is an important predictive indicator influencing the prognosis of PTCL patients and patients who experience anemia will be poor in prognosis.